Edible bird’s nest, a valuable glycoprotein source : current research prospects and challenges in Malaysia - Kevser Irfan Unal,; Chang, Lee Sin; Wan Aida Wan Mustapha,; Noorul Syuhada Mohd Razali,; Abdul Salam Babji,; Lim, Seng Joe (Penerbit Universiti Kebangsaan Malaysia, 2022)
Edible bird’s nest (EBN) is a salivary secretion of swiftlets which consist of protein and carbohydrate rich glycoproteins. This natural ingredient is very valuable, nutritional and medically valuable. The EBN industry have grown rapidly and benefited the Malaysian economy, hence, it is viewed seriously and it is actively supported by the government. This review discusses the progress and development of EBN industry as well as the R&D activities and endeavours especially that which involves deriving peptides with biological activities from EBN and its by-product sources. Many studies have documented the therapeutic properties of EBN such as antiaging, antiviral, antioxidant, and antihypertensive. Studies have also been conducted to produce glycoprotein hydrolysates from EBN through enzymatic hydrolysis, and findings showed that these bioactive peptides increase solubility as well as antioxidant and antihypertensive activities. Enzymatic hydrolysis breaks long protein chains at specific sites and releases amino acids and small peptides with lower molecular weights. The EBN hydrolysates produced can improve bioactivity and overcome insolubility and low absorption of EBN prepared and consumed through traditional means. Further studies need to be carried out to optimise EBN glycoprotein hydrolysates production as well as maximising their bioavailability and efficacy in the human gastrointestinal system. In addition, EBN by-products produced during EBN cleaning process should be fully utilised to recover the high-value glycoproteins, while reducing pollution and wastage. By enhancing R&D activities of EBN, bioactive glycopeptides produced from EBN may become an important functional food ingredient for various uses and innovative value-added products in the future.